Changes in biomechanical parameters under the feet while maintaining balance in basketball players before and after training - Vasilyev, R.; Vasilyeva, I. A.; Kovalev, A. A.; Vodopyanov, L. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of the nature of changes in the biomechanical parameters of the load under the foot and the postural status of basketball players under the influence of training.